Diversity and Abundance of Insect Polinators and Insects Visitor Flower on Magnolia spp Plants at Universitas Samudra - Aprilia Putri, Kartika; Al Fajar, Beni; Rosmaiti, Rosmaiti; Putri Endah sari, Herlina; Yusman Persada, Andri; Purnama Febri, Suri (Program Studi Biologi, Fakultas Teknik, Universitas Samudra, 2025)
Pollinator insects are insects that play a role in the pollination process, namely intermediaries in plant pollination. Magnolia spp plants are plants that contain secondary metabolite compounds which have the potential to be used as raw materials for medicines, cosmetics and perfume raw materials. The aim of this research was to determine the diversity and abundance of insect pollinators and flower visitors on Magnolia spp. at Universitas Samudra. The method used in this research is sampling using a purposive random sampling method with hand collecting techniques, identification and data analysis.The research results found 9 orders and 5 families from 139 individual insect pollinators and pollinators on Magnolia spp. The results of data analysis show that the H' value (1.72) is in the medium category, the C value (0.23) has low dominance, and the E value (0.19) shows low uniformity. Several factors influence the presence of pollinator insects and flower visitors, including flower availability, temperature and air humidity.